Using ferro-magnetic fluids to lubricate non-conformal isothermal contacts - Noronha De Souza, Petronio. (Cranfield University, 1993)
Magnetic fluids are synthetic materials that combine in a single medium the properties of fluids and magnetic materials. The action of a magnetic field on the magnetic fluid allows the design of new types of bearings and also provides conventional ones with new properties. This work presents a contribution to the study of the lubrication of linear isothermal non-conformal contacts with magnetic fluids under the action of a non uniform magnetic field perpendicular to the plane of the contact. The fluid is assumed to present extrinsic superparamagnetism. The regime of lubrication considered is the isoviscous-rigid. The analytical approach adopted considers small perturbations of the classical analytical solution already known for this type of contact. The main objectives of the work are: To establish the equations and assumptions that are necessary to treat the proposed lubrication problem To analyze the impact of the change in the apparent viscosity of the magnetic fluid on the thickness of the lubricating lm due to the presence of the magnetic field ° To develop an experimental technique able to deal with the problems that arise with the use of magnetic fluids in the lubrication of a two-disc machine The mathematical treatment of the proposed problem brings together the analytical methods adopted in fluid lm lubrication to the analysis of long isothermal hydrodynamic bearings and those from the magnetic-liquid fluid dynamics (ferrohydrodynamics) usually adopted to study the flow of magnetic fluids that present extrinsic superparamagnetism. The result is a coherent system of equations supported by a well defined set of assumptions. The solution obtained allows the study of the eventual change of the lm thickness that can be achieved by the application of a magnetic field across the contact. The work also discusses the experimental technique necessary to study the problem in a two-disc machine that runs with minute amounts of lubricant, applies a magnetic field across the contact and measures the lm thickness by a capacitance method. The work concludes by showing theoretically that the lm thickness can be either increased or reduced depending on the magnetic and viscous properties of the fluid and the intensity of the magnetic field. These conclusions are supported by experiments with a magnetic oil in a two-disc machine.